2019
DOI: 10.1016/j.ijpe.2019.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating contracts for VMI systems under manufacturer-CSR and retailer-marketing efforts

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The greater the green sensitivity leads to the market's demand response effect, which will encourage retailers to exert more green marketing efforts, thereby increasing product ordering. The studies of [8,43,44] proposed the same in their research work. Manufacturers will consider increasing the wholesale price for their profit maximization.…”
Section: Bank Loan Financing Strategymentioning
confidence: 97%
See 1 more Smart Citation
“…The greater the green sensitivity leads to the market's demand response effect, which will encourage retailers to exert more green marketing efforts, thereby increasing product ordering. The studies of [8,43,44] proposed the same in their research work. Manufacturers will consider increasing the wholesale price for their profit maximization.…”
Section: Bank Loan Financing Strategymentioning
confidence: 97%
“…This consumer preference will force retailers to adopt green marketing and promote corporate social responsibility. Phan et al confirmed that market demand is affected by retailers' green marketing efforts [43]. Mondal and Giri [44] constructed a two-period green closedloop SC model composed of a single manufacturer and a single retailer and studied the impact of green innovation, marketing efforts, and the recycling rate of waste products on SC decisions.…”
Section: Sc With Green Marketingmentioning
confidence: 99%
“…Generally, the market demand is sensitive to the prices in two channels and corporate environmental responsibility level [70][71][72][73][74]. The linear function is commonly used to describe the price or green sensitive market demand in the supply chain [73,[75][76][77][78][79].…”
Section: Demand and Profit Functionsmentioning
confidence: 99%
“…Raj et al (2018) study a supply chain in which the supplier is responsible for greening and the buyer is accountable for social responsibility and uses five different contracts to coordinate the channel. Phan et al (2019) investigate the coordination of a two-echelon supply chain with vendor managed inventory systems where the market demand is dependent on the retailer's marketing effort, retail price and the manufacturer's CSR effort.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%